Disaggregate energy consumption and industrial output in Pakistan: An empirical analysis - Ahmer Qasim Qazi; Khalid Ahmed; Muhammad Mudassar (Kiel Institute for the World Economy (IfW), 2012)
The study concentrates on the relationship between disaggregate energy consumption and industrial output in Pakistan by utilizing the Johansen Method of Cointegration. The results confirm the positive effect of disaggregate energy consumption on industrial output. Furthermore, bidirectional causality is identified in the case of oil consumption, whereas unidirectional causality running from electricity consumption to industrial output is observed. Moreover, unidirectional causality has been noticed from industrial output to coal consumption although there is no causality between gas consumption and industrial output. It is obvious that conservative energy policies could be harmful to the industrial production; therefore, the government has to develop innovative energy policies in order to meet the demand for energy. Additionally, the government has to pay serious attention to alternative energy sources such as solar and wind in order to boost the clean industrial growth.
Keywords: C32; Q42; 330; disaggregate energy consumption; industrial output; Johansen cointegration test; Energiekonsum; Industrielle Produktion; Kointegration; Schätzung; Pakistan